Pengaruh Latihan Shuttle-Run dan Zig-Zag Run terhadap Kelincahan Atlet Taekwondo - Citra Azhariat Malasari (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga, 2019)
The purpose of this study was to determine the effectiveness of shuttle run and zig-zag run exercises in increasing the agility of taekwondo athletes. This study uses a quasi-experimental method with a pre-test and post-test design control group design. The results showed, (1) shuttle run training had a significant effect on increasing agility (thit = 61.42> ttab = 2.26); (2) ziq-zaq run exercises have a significant effect on increasing agility (thit = 169.06> ttab = 2.26); (3) ziq-zaq run exercises are more effective in increasing agility compared to shuttle run exercises (thit = 25.64> ttab = 2.26). In conclusion, training with the zig-zag run method is more effective in increasing the agility of taekwondo athletes. Keywords: Shuttle-Run, Zig-Zag Run, Agility, Taekwondo.